How patients use repeat antibiotic prescriptions: the impact of dosing directions - Thompson, Angus; Peterson, Gregory; Bindoff, Ivan; Stafford, Andrew (Wiley-Blackwell, 2017)
Background: Repeat prescribing of antibiotics is widespread in Australia. This may be associated with risks to individual patients and contribute to inappropriate antibiotic use.